The Effects of Application Vinasseand additive nitrogen and phosphorus on Growth and Yield of Tomato - Ahmad Golchin; Amin Vatani; Behnam Salvand; Fatemeh Rakhsh (Majallah-i ̒Ulum-i Bāghbānī, 2017)
Introduction:Vinasse is a byproduct of the sugar industry. Sugarcane or Sugarbeet is processed to produce crystallinesugar, pulp and molasses. The latter isfurther processed by fermentation to ethanol, ascorbicacid or other products. After the removal of the desired product (alcohol, ascorbicacid, etc.) the remaining material is called vinasse. Vinasse is sold after a partial dehydration and usually has a viscositycomparable to molasses. Commercially offered vinasse comes either from sugarcaneand is called cane-vinasse or from sugarbeet and is called beet-vinasse. On average, for each liter of vinasse, 12 liters alcohol produced. Vinasse is a material with dark brown color and the smell of burned sugar, which is rich in potassium, calcium, magnesium, phosphorus and nitrogen. Materials and Methods:To determine the effect of vinasse and additive nitrogen and phosphorus on growth and yield of tomato, a factorial pot experiment was conducted at ZanjanUniversity in 2008. Two different plant nutrient including N and P and their combination (N+P) were added to vinasse with three different concentrations to form experimental treatments. In addition to these treatments, three control treatments with vinasse of different concentrations, but with no additive were also included in the experiment. Each treatment used with two different application methods (soil application and soil + foliar application).The experiment had 24 treatments, a complete randomized design and three replications. The vinasse used in this experiment was diluted with water 10, 20 and 40 times to make a nutrient solution of three different concentrations of tomato plant. The amounts of nitrogen and phosphorus that were added to vinasse were 224 and 62 mg/l, respectively. Phosphorus and nitrogen were applied to as super-phosphate triple and calcium nitrate and ammonium nitrate respectively. After being deployed to ensure complete installation of tomatoes in pots containing perlite (about 2 weeks after the transfer of seedlings tothe pots) treatments wereapplied to the pots. It should be noted that initially, three tomato seedlingswere planted in each pot at later stage after the plants were thinned to one plant per pot.Five months later after planting seedlings, fruits were picked and measured separately. At the end of the growth period, fruit yield, leaf and some quality characteristicsof fruit were measured. Results Discussion: The results showed that the effects of vinasse concentrations on fruit yield, dry matter content of fruit, dry weight of root and plant height were significant at p